Analisa Audit Energi Listrik di PT. Ispat Bukit Baja Kota Bekasi - Sulistyowati; Ar Raafi Pangestu; Sigit Setya Wiwaha (Politeknik Negeri Malang, 2022)
An audit energy needs to be carried out because the value of Energy Consumption Intensity in 2020 is 251 kWh / m2 / year and in 2021 it is 221 kWh / m2 / year and the value of Specific Energy Consumption in 2020 is 0.26 GJ / Ton and in 2021 is 0.29 GJ/Ton. The energy audit method used is to calculate the value of Energy Consumption Intensity and Specific Energy Consumption. The savings opportunities made are on the air conditioning system, lighting system, and electric motor load. From the results of the analysis and calculation of savings in the air conditioning system, savings of 50.1% or 67.70 kWatt were obtained using a psychrometric diagram to determine the cooling system according to the needs of the room, then for the lighting system, savings of 21.9% or 6 kWatt by replacing the installed lighting system with energy-saving lamps, then the load of the electric motor is using capacitor to improve the power factor value which was originally 0.77 to 0.85 with the aim that the motor speed does not change which will result in the precision of the production obtained savings in the use of apparent power of 7.13% or 126.52 kVA. The total recommended power saving obtained from the calculation results is 73.7 kWatt. So based on the calculation of the energy audit that has been done, it can reduce production costs and energy use efficiency